Medicaid, family spending, and the financial implications of crowd-out - Marcus Dillender (W.E. Upjohn Institute for Employment Research, 2017)
A primary purpose of health insurance is to protect families from medical expenditure risk. Despite this goal and despite the fact that research has found that Medicaid can crowd out private coverage, little is known about the effect of Medicaid on families' spending patterns. This paper implements a simulated instrumental variables strategy with data from the Consumer Expenditure Survey to estimate the effect of an additional family member becoming eligible from Medicaid on family-level health insurance coverage and spending. The results indicate that an additional family member becoming eligible for Medicaid increases the number of people in the family with Medicaid coverage by about 0.135 to 0.142 and decreases the likelihood that a family has any medical spending in a quarter by 2.7 percentage points. As previous research often finds with different data sets, I find evidence that Medicaid expansions crowd out some private coverage. Unlike most other data sets, the Consumer Expenditure Survey allows for considering the financial implications of crowd-out. The results indicate that families that transition from private coverage to Medicaid are able to spend significantly less on health insurance expenses, meaning Medicaid expansions can be welfare improving for families even when crowd-out occurs.
Keywords: D12; I13; 330; Medicaid eligibility; crowd-out; family spending